2007
DOI: 10.1007/s00167-007-0386-9
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic all-inside repair of Palmer type 1B triangular fibrocartilage complex tears: a technical note

Abstract: Arthroscopic repair of peripheral dorso-ulnar triangular fibrocartilage complex (TFCC) lesions is now a preferred method. Both outside-in and inside-out techniques are commonly performed for repairing Palmer type 1B TFCC tear. But these techniques have disadvantages of making an additional skin incision to tie knots subcutaneously over the capsule. We performed an arthroscopic all-inside repair technique of Palmer type 1B TFCC tears, which is a modified method of the outside-in technique using a spinal needle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…16,22,29 Although this is one viable option for repair, other techniques such as the all-inside arthroscopic technique can be used. 48,49 This might be relevant based on Yao's belief that all-inside sutures are superior due to less residual ulnar pain from subcutaneous knots when compared with other suture techniques. 50 Therefore, the results of our study comparing arthroscopic repair to USO have to be taken in perspective considering that different surgical techniques exist in the surgical treatment of TFCC tears.…”
Section: Discussionmentioning
confidence: 96%
“…16,22,29 Although this is one viable option for repair, other techniques such as the all-inside arthroscopic technique can be used. 48,49 This might be relevant based on Yao's belief that all-inside sutures are superior due to less residual ulnar pain from subcutaneous knots when compared with other suture techniques. 50 Therefore, the results of our study comparing arthroscopic repair to USO have to be taken in perspective considering that different surgical techniques exist in the surgical treatment of TFCC tears.…”
Section: Discussionmentioning
confidence: 96%
“…37 Other prior studies have demonstrated methods to pass suture through the TFCC and capsule all-arthroscopically with the knot tied intra-articularly with various cannulated passing devices. 16,[38][39][40] Millants et al reported a technique using intra-articular knots on two pieces of suture used to tether the peripheral TFCC, which was secured to the ulnar wrist capsule with a third knot tied subcutaneously in the 6U portal. They reported mean DASH scores of 15 at 4.8 years of follow-up with 46% of patients still reporting some limitation on their activities due to their wrist.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 15 described an all-inside repair using a 20-guage spinal needle, arthroscopic retriever, and suture material. Preliminary results of four patients at 7 month follow-up demonstrated no ulnar joint line tenderness and negative grind test.…”
Section: Trend Toward All-inside Arthroscopic Techniquementioning
confidence: 99%